Astronomy and Experimentation. - Sandell, Michelle (Techné: Research in Philosophy & Technology)
In this paper I contest Ian Hacking's claim that astronomers do not experiment. Riding on this thesis is a re-evaluation of his view that astronomers are less justified than other natural scientists in believing in the existence of the objects they study, and that astronomers are not proper natural scientists at all. The defense of my position depends upon carefully examining what, exactly, is being manipulated in an experiment, and the role of experimental effects for Hacking's experimental realism. I argue that Hacking's experimental realism is not adequately defended, and even if we accept it in good grace, the case can be still made that astronomers experiment by Hacking's account.